Faded Aattitude Nationalism Generation Millennialsto Education Pancasila and Citizenship - Selly Aprillia Ningsih (International Journal of Students Education, 2024)
This study aim for know reason it faded attitudenationalism of the millennial generation while knowing how to ways that can arouse their nationalist attitudes through Education Pancasila and citizenship as well as roles family,education, and the government in awakening the spirit of nationalism. The method used in this research is literature study by referring to sources such as journal articles, books and articles from the Internet. The results of this study indicate that the cause of the fading the nationalist attitude of the millennial generation is caused by 2 factors: factors internal and factor external. Factor internal covers there is flavor disappointed from in self a millennial, for example flavor disappointed to performancegovernment. External factors include the development of globalization which cause lots change. Method grow attitude Millennial generation nationalism can be done by getting used to it using domestic products, providing insight into the importance of having a spirit of nationalism, as well as equipping them with give material about attitude nationalism and defend country through education pancasila and citizenship.